Efektifitas Pembelajaran dengan Model Contextual Teaching Learning (CTL) Untuk Meningkatkan Hasil Belajar Fisika di kelas X Pada Konsep Besaran dan Pengukuran - Marwiya Muksin (Peneliti.net, 2019)
This study aims to determine the effectiveness of improving physics learning outcomes by applying the CTL (contextual teaching learning) learning model to the concepts of quantity and units. This type of research is an experimental study with a village pretest-posttest control group design. The population in this study were all students of class X IPA of SMA N 8 Tikep totaling 44 students spread over 2 classes, the sample in this study was a portion of a population of 22 students with cluster sampling techniques. Having obtained 2 classes as samples then randomized to determine the experimental class and the control class. Data collection in this research is to use the test. The test is done before and after learning. The results of this study indicate that: (1) in the control class the average pretest value was 54.35 while the posttest mean score of 74.76 was still lower than the experimental class, (2) in the experimental class the average pretest value was 68.43 while the average posttest score of 81.56 is higher than the control class, (3) the average posttest score of the experimental class> control class is 81.56> 74.76 which means the experimental class learning outcomes are higher than control class, in paired t-test, the result obtained is sig.2 tailed at 0,000 <0.05 using the CTL (contextual teaching learning) model on the concept of Quantity and Measurement more effectively